Viromes of Three Phyla of Aquatic Organisms in the South China Sea - Qian Wen; Jun Wang; Lihui Dai; Abulimiti Moming; Zhaojun Fan; Yi Huang; Yingying Ge; Fei Deng; Hualin Wang; Feifei Yin; Shu Shen (Zoonoses)
This study was aimed at investigating the viral diversity associated with marine organisms in the South China Sea, to improve understanding of the region’s viral ecosystems. Viruses profoundly influence aquatic ecosystems, by affecting marine biogeochemical cycles and posing threats to marine organisms. Nonetheless, a comprehensive study of marine organisms’ viral diversity in the South China Sea remains lacking. We collected gill and viscera tissue samples from three marine phyla ( Chordata , Arthropoda , and Mollusca ) along the South China Sea coast. High-throughput sequencing and bioinformatics analyses were conducted to identify and characterize viral communities within these samples, with a focus on both viral composition and potential zoonotic threats. We observed distinct viral composition patterns across tissues and phyla, notably involving Adintoviridae and viruses within the Herpesviridae and Dicistroviridae . The presence of zoonotic viruses in economically important aquatic organisms suggests potential risks. This study contributes to broader understanding of viral diversity, by suggesting potential epidemic causes and illustrating genetic relationships among viruses associated with marine organisms. By extending the virus distribution map for this region, our findings underscore the need to consider the viral microenvironments surrounding marine species, and their implications for marine and human health.